Bilateral True Giant Aneurysm of the Profunda Femoral Artery: Case Report and Review of the Literature - Alessandro Robaldo; Mauro Maselli; Daniele Maggio (Case Reports in Surgery)
We report a rare case of a bilateral true giant aneurysm of the profunda femoral artery aneurysms (PFAAs) in a 80-year-old man with a previous history of “open” abdominal aortic surgery and small bilateral popliteal artery aneurysm. In the English Literature only seven previously cases of true bilateral PFAAs are reported. Due to its location, this lesion may require surgical intervention and removal. The presentation, the diagnostic evaluation, and the surgical management of the aneurysm are discussed.